Perbandingan Hasil COVID-19 Metode Rapid Antigen Test dengan PCR: Literature Review - Siti Rachmawati; Yuanita Windusari; Hamzah Hasyim (Universitas Batanghari Jambi, 2022)
The basis for the identification of SARS-CoV-2 cases in handling the COVID-19 pandemic is Reverse Transcriptasi Polymerase (RT-PCR) and the SARS-CoV-2 specific rapid antigen test. RT-PCR test takes a long time and expensive to get results, while the SARS-CoV-2 rapid antigen test is a simple and fast alternative in getting COVID-19 detection results. The method used is descriptive observational in the form of a literature review by reviewing the existing literature. Several screening and confirmatory tests are available to detect SARS-CoV-2. Screening tests such as the Rapid Antigen Test (RAT) can identify high-risk populations. RAT reduces dependence on RT-PCR, where the cost of the RT-PCR kit and technical expertise is a major concern. Precise and sensitive molecular technique that quantitatively detects viral RNA from clinical specimens. RAT for COVID-19 showed lower sensitivity than RT-PCR for both symptomatic (single or multiple symptoms) and asymptomatic infections.